THE INFLUENCE OF FINANCIAL ATTITUDE, FINANCIAL BEHAVIOR, FINANCIAL KNOWLEDGE, AND FINANCIAL SOCIALIZATION ON FINANCIAL LITERACY IN EMERGING ADULTS IN BANTEN PROVINCE - Sandi, Marcellinus Antony; Yanuarti, Ika (ULTIMA Management, 2024)
Abstract-Based on data from the Financial Services Authority (OJK), the level of financial literacy in Indonesia is still lower than the national level of financial inclusion. The gap between the level of financial literacy and the level of financial inclusion indicates that people have access, but do not yet understand and utilize the available financial information. Financial literacy can be improved through internal factors; financial attitude, financial behavior, & financial knowledge, and external factors with financial socialization conducted by socialization agents; parents, peers, school, & technology/media. The population in this study was a group of emerging adults in Banten province and the number of samples selected was 207 respondents. The purpose of this research is to determine the influence of internal factors and external factors on the level of financial literacy. The results of the research show that there is a positive influence between financial attitude, financial behavior, financial knowledge, and financial socialization technology/media on financial literacy in emerging adults in Banten province, so that financial literacy can be improved by improving financial attitude, financial behavior, financial knowledge, and financial socialization through technology/media. Keywords: Financial Literacy; Financial Socialization; Financial Attitude; Financial Behavior; Financial Knowledge